Shading Influence of Sengon (Falcataria moluccana L.) and Fertilization against White Ganyong Growth (Canna edulis Ker.) - Nurheni Wijayanto; Suyogia Nur Azis (Jurnal Silvikultur Tropika, 2013)
Sengon (Falcataria moluccana L.) public forests is still becoming planted by Monoculture system. Alternative solution to optimalize the use of land is agroforestry system. Agroforestry system gives income benefits in non timber product. This research aims to measure shading influence of sengon, kinds of fertilizer, and dosages of organic fertilizer against white ganyong growth. The shading treatments consist of the open area (shade intensity 0%) and sengon shaded area (shade intensity 42%). The fertilizer treatments consist O0 (no fertilizer as control), O1 (POC 350 mL/ha, 450 mL/ha), O2 (POC 700 mL/ha, 900 mL/ha), O3 (POC 1400 mL/ha, 1800 mL/ha) and NPK. The experiment was analyzed by nested design. The results showed that growth of white ganyong on sengon shaded area is higher than open area to parameters hight of plant, length of leaves, width of leaves and plant biomass. Treatments of shading and fertilization did not significantly affect to tuber wights of white ganyong.Key words: agroforestry, Canna edulis, Falcataria moluccana, fertilization, shading